Exploring the purpose and types of home glass accessories: sustainability, transparency, aesthetics, and durability / Radwa Bahaa Elsayed, Hema Zulaika Hashim and Mohd Shahril Rusman - Elsayed, Radwa Bahaa; Hashim, Hema Zulaika; Rusman, Mohd Shahril (Faculty of Art and Design, 2024)
Glass is omnipresent in applications from packaging to prosthetics, and building to telecommunications, resulting in significant glass waste. This study examines the purpose and various types of home glass accessories and aims to minimize waste through recycling and the development of sustainable products that meet market demands. The research employed interviews with glass designers and a systematic literature review as the primary exploration techniques. The findings provide valuable insights into the sustainability, transparency, aesthetics, and durability of home glass accessories. The literature review revealed that glass is extensively used due to its transparency, chemical inertness, environmental friendliness, availability, and affordability. Glass recycling offers benefits such as conserving natural resources, reducing waste, saving energy, and decreasing air and water pollution. However, certain glass products have a limited lifespan, contributing to waste generation. The interviews revealed that people choose glass products for their transparency, chemical stability, decorative appeal, ease of cleaning, and sustainability. Kitchenware, bottles, containers, lighting units, vases, antiques, and serving ware were identified as common types of home glass accessories. Lighting lamps and vases were found to be the most popular functions.